A Nation of Villages : Riot and Rebellion in the Mexican Huasteca, 1750-1850 - Ducey, Michael Thomas, 1960- (Book collections on Project MUSE., 2004)
"During the period 1750-1850, republican national institutions slowly replaced colonial and monarchical rule. This was a turbulent time in rural Mexico. It was a period of political instability marked by violent peasant rebellions that were longer and more violent and that involved more people than those that occurred in the colonial era. Mexican villagers became skilled insurrectionists." "In this book, Michael Ducey analyzes the peasant rebellions in Mexico's Huasteca region over that time, beginning with short-lived colonial riots, progressing through a long and brutal insurrection associated with the war of independence and several region-wide uprisings, and culminating in the "Caste War of the Huasteca" of the 1840s. He asks not just why villagers revolted but how their discontent fit into the political drama of early national Mexico."--Jacket.